Egg Market Integration and Financial Feasibility Laying Hens Farmer in Central Java, Indonesia - Agus Setiadi; Siswanto Imam Santoso; Zenaida Sumalde (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
The research aims to determine the degree of chicken egg market integration, determine the price asymmetric and determine the financial feasibility of chicken egg business in Central Java, Indonesia. Secondary data from January 2017- December 2019 was used for research. Survey research was conducted on 100 (one hundred) laying hens farmers. The research study was conducted in Semarang city, Kendal regency and Semarang regency. Johansen test, Pearson correlation and Granger Causality test were used in this study. Financial feasibility analyses such as investment, payback period (PP), net present value (NPV), Internal Rate of Return (IRR), Return on Investment (ROI), and Benefit-cost (B/C) ratio are used in this study. The result showed there was a positive correlation between the Price in Kendal Regency and Semarang City. Increasing prices in Semarang City caused the increasing Price in Kendal regency vice versa. There was a marketing integration between Semarang city and Kendal regency, and Granger Causality showed Price in Semarang city influenced the Price in Kendal regency and Semarang regency. The price of chicken eggs in Semarang city, Kendal regency, and Semarang city were symmetric. Based on the calculation of PP, NPV, IRR, ROI and B/C ratio, laying hens business in Central Java is feasible to run.